(untitled) (Fiep Bulletin - online, 2013)
Heart failure (HF) is, among all not transmissible chronic disease, the most troubling in healthcare around the world. Although there are great advances in medicine over the past five decades, nowadays, mortality reaches more than 50% of confirmed cases in five years, after the confirmation of the diagnosis. Educational measures, therapeutic, pharmacological and nonpharmacological should be encouraged, since the IC is a crippling disease and decreases the quality of life of the patient. The aim of this study was to present a vision of the quality of life of patients with IC as the prescription drug in a health facility. This was a retrospective cross-sectional study conducted in a basic health unit (BHU) of Maringá, Paraná, whose data were collected from medical records of patients with heart failure. For inclusion in the sample, the medical records should include the drug digoxin. As a result it was observed a higher prevalence in women (56.92%) compared to men whose mean age was 68.95 ± 13.2, the highest concentration of age group of patients was between 71 to 80 years and it was found that 187 drug prescriptions make possible the harm adverse effects to patients with HF. This study concluded that the quality of life of HF pacients can be reduced by the medication used.